Pengaruh Quantum Memori dan Quantum Learninng dalam Meningkatkan Mutu Pendidikan di MTs YLPI Sukabumi - Abdul Fajar; Kun Nurachadijat (Jurnal Akuntan Publik, 2023)
This study aims to find out how the application of Quantum Memory and Learning in Islamic Religious Education Learning at MTs YLPI Sukabumi. So this research is a field research with a qualitative approach using descriptive analysis.The variables studied are divided into two, namely the independent variable is the application of Quantum Memory and Learning and the dependent variable is the learning of Islamic Religious Education.All primary data needed in this study were obtained through the main instrument in the form of questionnaires / questionnaires, while observations, interviews, were used to complete the required data. All collected data is then processed and analyzed using descriptive analysis.The results of this study prove that the concept of Quantum Memory And Learning applied by teachers is the AMBAK Technique (What are the Benefits for Me), structuring the learning environment, cultivating a champion attitude, freeing up learning styles, getting used to taking notes, getting used to reading, making children more creative, training children's memory strength. The application of Quantum Memory And Learning to Islamic education learning at MTs YLPI Sukabumi is quite good. This can be seen by the indicator of 39 respondents from students with 74% saying that the application of Quantum Memory And Learning applied by teachers to Islamic education learning is quite good and the application of Quantum Memory And Learning is also able to improve student learning outcomes. This can be seen from 59% of students who say student learning outcomes are very good through the application of Quantum Memory And Learning. However, based on all data, both questionnaires and interviews, it shows that the application of Quantum Memory And Learning still needs to be improved again because it sees that there are still teachers who have not been able to apply Quantum Memory And Learning to Islamic Religious Education learning at MTs YLPI Sukabumi. Keywords: Implementation, Quantum Memory, Quantum Learning.